Profile of leptin, adiponectin, and body fat in patients with hyperprolactinemia: Response to treatment with cabergoline - Pala, Nazir Ahmad (Indian J Endocrinol Metab, 2016)
INTRODUCTION: Though hypoadiponectinemia and leptin resistance have been proposed as potential factors for weight gain in patients with hyperprolactinemia (HPL), the effects of HPL and cabergoline on these adipocyte-derived hormones are not clear. Aims of this study were (i) to assess the alterations of body fat, leptin, and adiponectin in patients with HPL (ii) effect of cabergoline treatment on these parameters. METHODS: Nineteen consecutive patients with prolactinoma (median prolactin [PRL] 118.6 (interquartile range: 105.3) μg/L) and 20 controls were studied in a nonrandomized matched prospective design. The controls were age, gender, and body mass index (BMI) matched. Anthropometric data, metabolic variables, leptin, and adiponectin were studied at baseline and 3 and 6 months after cabergoline treatment. RESULTS: Patients with prolactinoma had increased level of fasting plasma glucose (P < 0.001) as compared to age-, gender-, and BMI-matched healthy controls. Estradiol concentration of controls was higher than that of patients (P = 0.018). Patients with prolactinoma had higher levels of leptin (P = 0.027) as compared to healthy controls without a significant difference in adiponectin levels. There was a significant decrease of body weight at 3 months (P = 0.029), with a further decline at 6 months (P < 0.001) of cabergoline therapy. Furthermore, there was a significant decrement of BMI (P < 0.001), waist circumference (P = 0.003), waist-hip ratio (P = 0.03), total body fat (P = 0.003), plasma glucose (P < 0.001), leptin levels (P = 0.013), and an increase in estradiol concentration (P = 0.03) at 6 months of cabergoline treatment. CONCLUSION: Patients with prolactinoma have adverse metabolic profile compared to matched controls. Normalization of PRL with cabergoline corrects all the metabolic abnormalities.